SHOCK PROTECTION DEVICE FOR ROTATION SENSORS - Stelian ALACI; Florina Carmen CIORNEI; Dumitru AMARANDEI; Constantin FILOTE; Simion PĂTRAŞ-CICEU; Dorel PRODAN (Fiabilitate şi Durabilitate)
Starting form a virtual model of a device designed to investigate friction force effects in colliding mechanical systems, the authors have developed a test-rig. The friction force effects had to be estimated using a rotating sensor. Finally, to protect the sensor from shock effects, a constructive solution is proposed. The accuracy of the new device is estimated using FE analysis.